2006
DOI: 10.1381/096089206778663797
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Laparoscopic Sleeve Gastrectomy as a Revision Procedure for Prior Laparoscopic Gastric Banding

Abstract: LSG proved to be feasible and safe after LAGB. Longer follow-up and larger series are needed to assess weight loss results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0
5

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(54 citation statements)
references
References 17 publications
3
46
0
5
Order By: Relevance
“…Bernante has described a small cohort of eight patients who underwent a laparoscopic sleeve gastrectomy I, in three for esophageal dilatation and in five for unsuccessful weight loss. Although the operation only took an average of 90 minutes, without conversions and complications, the follow-up was too short to conclude on the final results [28]. It is believed that, for patients in the range of 40 kg/m 2 , a drop of 10 BMI points might be expected, as this has been seen in revised DS patients [13].…”
Section: Discussionmentioning
confidence: 99%
“…Bernante has described a small cohort of eight patients who underwent a laparoscopic sleeve gastrectomy I, in three for esophageal dilatation and in five for unsuccessful weight loss. Although the operation only took an average of 90 minutes, without conversions and complications, the follow-up was too short to conclude on the final results [28]. It is believed that, for patients in the range of 40 kg/m 2 , a drop of 10 BMI points might be expected, as this has been seen in revised DS patients [13].…”
Section: Discussionmentioning
confidence: 99%
“…However, BPD, AGB, and other operations also have been used in this setting [231][232][233]. Likewise, most authors advocate RGB for revision of AGB because of complications or insufficient weight loss [217][218][219], although other operations have been applied [234,235]. Finally, in cases of failed BPD ?…”
Section: Anatomic Failurementioning
confidence: 99%
“…Several technical options are offered as an alternative to failed VBG: Revision VBG, conversion to Roux-en-Y gastric bypass, to gastric banding and recently to SG. 8,14,[19][20][21][22][23] Studies have shown that SG is safe and effective in achieving adequate weight loss in most patients. 24,25 We performed Roux-en-Y gastric bypass in one and SG in two patients with failed VBG.…”
Section: Discussionmentioning
confidence: 99%